PENGEMBANGAN LKS BERBASIS MASALAH BERBANTUAN CONCEPT MAPPING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA MADRASAH TSANAWIYAH - Safnowandi Safnowandi; Ismail Efendi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2017)
Abstract : This study aims to obtain problem-based LKS product concept-assisted mapping and to determine the improvement of cognitive learning outcomes. This research will be based on biodiversity material in grade VIII junior high school. This research is a development research. Researchers use 4-D development type (Four D Model) which consists of 4 stages: definition stage, design stage, development stage and disseminate stage. But this research is only three stages, namely the definition (define), the planning stage (design), the development stage (develop). This is because the implementation of the disseminate stage requires a long process and time. While the quality of Student Worksheet (LKS) that will be described include LKS feasibility, LKS effectiveness in terms of student cognitive learning outcomes and LKS practicality in terms of student responses. The instrument used in this research is validation sheet to know the feasibility of LKS and questionnaire for student response. The data of students' cognitive learning achievement is obtained through pretest and posttest result. This LKS has practical and effective characteristics used in learning. The results showed that the development of LKS validation results from the content / material experts obtained an average score of 4, so that the LKS declared feasible. Post-test results show that the percentage of mastery is 87%, so the problem-based LKS on the subject of biodiversity can be said to be effective. While the developed LKS obtained a score of questionnaire responses of students of 3.11 so it can be concluded that LKS practical. So it can be concluded that the problem-based LKS assisted concept mapping developed feasible to use.